2002
DOI: 10.1002/jsfa.1227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of muscle biochemical constituents on the meat texture of cultured yellowtail (Seriola quinqueradiata) at different anatomical locations

Abstract: A study was conducted to evaluate meat texture (breaking strength), muscle proximate composition and muscle collagen content at three anatomical locations in cultured yellowtail. We report here the contribution of muscle biochemical constituents to the raw meat texture of cultured yellowtail, and the variation in muscle biochemical composition as well as meat texture with the anatomical location of the meat. Meat breaking strength decreased significantly with the anatomical location of the meat from head to ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 33 publications
5
28
1
Order By: Relevance
“…This result is in agreement with previous reports on cultured yellowtail [13,14]. We also observed a similar correlation between muscle lipid content and moisture content in a previous study on cultured yellowtail [6]. Our results showed that there was no correlation between muscle lipid content and protein content in amberjack (data not shown), which is in contrast to the significant negative correlation observed between muscle lipid content and protein content in cultured yellowtail [6].…”
Section: Statisticssupporting
confidence: 74%
See 4 more Smart Citations
“…This result is in agreement with previous reports on cultured yellowtail [13,14]. We also observed a similar correlation between muscle lipid content and moisture content in a previous study on cultured yellowtail [6]. Our results showed that there was no correlation between muscle lipid content and protein content in amberjack (data not shown), which is in contrast to the significant negative correlation observed between muscle lipid content and protein content in cultured yellowtail [6].…”
Section: Statisticssupporting
confidence: 74%
“…The mean individual fish weight ranged from 2367 to 4007 g with overall mean value of 3414 g. The mean individual fish length ranged from 59.3 to 69.7 cm with an overall mean value of 64.4 cm. It should be noted that the mean individual fish weight of cultured amberjack sampled during this study was lower than that of the cultured yellowtail sampled in an earlier study [6]. Since fish of both species were procured from the same retailer, we conclude that the marketable size of cultured amberjack is smaller than that of the yellowtail.…”
Section: Statisticsmentioning
confidence: 70%
See 3 more Smart Citations